Complexos de vanádio(V) derivados de trifenilfosfônios e hidrazidas: avaliações estruturais, interações com dna e hsa e potencialidades citotóxicas - Martins, Francisco Mainardi (2023)
The development of new drugs and prodrugs with antiprotozoal, antibacterial, and antineoplastic therapeutic actions is currently focused on non-covalent and reversible interactions with deoxyribonucleic acid. In this effort, it is also essential to evaluate the interactions of these compounds with human serum albumin, a blood plasma protein that influences the pharmacokinetics of drugs. One possibility to develop more effective therapeutic drugs is mitochondrial targeting through derivatization of ligands with triphenylphosphonium groups. Among the compounds with antineoplastic activity studied are those containing vanadium, a naturally abundant metal present in enzymes, in addition to having proven physiological properties. In this context, the following work aims to synthesize aldehydes containing triphenylphosphoniums groups and, based on their derivation with hydrazides, synthesize and broadly characterize vanadium coordination compounds. After synthesis and characterization, the objective is to evaluate the interactions of these complexes with calf thymus deoxyribonucleic acid and human serum albumin using different spectroscopic techniques and molecular docking. Furthermore, the objective is to evaluate the in vitro cytotoxicity of these compounds against non-cancerous human epithelial cells of the HaCaT lineage. In this way, three aldehydes derived from triphenylphosphane, tris(4-fluorophenyl)phosphane and tris(4-methylphenyl)phosphane ([AH]Cl, [AF]Cl and [AC]Cl, respectively) were synthesized. From these aldehydes and five aromatic hydrazides, thirteen vanadium complexes (C1–C13) with imine hydrazone ligands O,N,O ([H2L1]Cl–[H2L13]Cl) were obtained. All complexes had their solid-state structures elucidated by single crystal X-ray diffraction and characterized by complementary techniques, evidencing the formation of pentacoordinated cis-dioxidovanadium(V) species. Thus, it was possible to define the coordination geometries and their degrees of distortion, as well as the neutral zwitterionic natures of the complexes. By solution characterization of the complexes, especially 1H, 19F, 31P, and 51V-nuclear magnetic resonance, structures in solution similar to solid-state structures were evident. Regarding biological applications, it was found that C1–C5 interact moderately and preferentially with minor grooves of calf thymus DNA and with site III of human serum albumin. While such complexes perform different types of interactions with the protein, they only perform van der Waals interactions with DNA. Regarding cytotoxicity, C1–C5 decrease cell viability proportionally to their concentrations (except C3) and through cell apoptosis.